Values and Attitudes to Ethnic Culture and Traditions as Predictors of Subjective Well-Being Among Russians and Kazakhs - Rail М. Shamionov; Nassiya Zh. Sultaniyazova (Российский психологический журнал, 2018)
Introduction. The article discusses the results of the study of the predictors of subjective well-being among representatives of two ethnic groups – Russians and Kazakhs from Russia and Kazakhstan. Values are the product of social creativity; they determine the type of adaptation, and also variations in the subjective well-being of the individual. This process occurs indirectly, through the correspondence of values and the realized activity. The main purpose of this study is to analyze values and attitudes to ethnic culture and traditions as predictors of subjective well-being.